Functional Results of Valgus Intertrochanteric Osteotomy in MalunitedIntertrochantertic Fractures (Journal of Fatima Jinnah Medical University, 2018)
Objective: To evaluate the functional results of valgus intertrochanteric osteotomy in the intertrochanteric fractures united in varus malposition.Study Design: Prospective StudyPlace and Duration of Study: The present study was conducted in Orthpaedic Unit 2 Jinnah Hospital Lahore(Allama Iqbal Medical College ) between Mar 2012 to Sep 2015.Material and Methods: A total 36 patients between 55-65 years of age with female to male ratio 3:1were included in the study. All the patients were suffering from neglected intertrochanteric fractures that were treated by the local bone setters in the peripheral remote areas of Punjab. The fractures united in the varus position. All the patients were treated by valgus intertrochanteric osteotomy and fixation with Dynamic hip screw with side plate.Results: There were 27female patients and 9 males ( F-M 3:1) All the patients were evaluated according to the Harris hip score ( HHS)preoperatively and postoperatively. Harris hip score improved from below 40 (poor) to 92( excellent) in 30 patients and 85( good) in 6 patients.Conclusion: As far as the varusmalunion of intertrochanteric fracture is concerned. Valgus intertrochanteric osteotomy is an excellent procedure to regain the better functional outcome at the hip joint.
Keywords: Valgus intertrochanteric Osteotomy, Dynamic Hip Screw (DHS)